Heart Full of Thrombi: Post COVID-19 multisite thrombosis assessed by echocardiography and pulmonary CT - Mitevska I; Grueva E; Kandic E; Busletik O (Akadémiai Kiadó, 2021)
Thrombosis in general, and especially venous thromboembolism (VTE) is one of the most common complications associated with COVID-19 infection. We present a 48 years old male patient with dyspnea and severe multisite post Covid-19 disease thrombotic complications, with pattern never seen before, that includes both ventricles, pulmonary arteries and peripheral vein involvement, assessed by echocardiography, vascular ultrasound and pulmonary CT angiography.